Main methods of the impact of the kazakhstan russian-language media on modernization - Eleonora Khankishiyeva, Almagul Zadayeva, Valentina Zhumagulova, Gulzhan Kazhigaliyeva, Aigul Onalbayeva, (Opción, 2019)
The study aims to investigate the main methods of impact of the Kazakhstan Russian-language media on modernization of public consciousness via comparative qualitative research methods. As a result, the methods that affect the modernization of public consciousness can also be attributed to the imaginary choice. The essence of the impact is based on the fact that readers are informed about two opposed ways to solve the problem or two positions on one issue. In conclusion, the Patriotic act and the idea Mangilik El (Eternal country), as well as the program Rukhani Zhangyru aimed at the modernization of public consciousness.